The Effect of The World Uncertainty Index on Cash Holdings in Indonesian Public Companies - Juan Adhitya Fatah (Manunggal Halim Jaya, 2026)
This study aims to examine the effect of the World Uncertainty Index (WUI)—a global measure of economic and policy uncertainty—on the cash holdings of publicly listed non-financial companies in Indonesia. Given the increasing global economic and geopolitical uncertainty, understanding how firms in emerging markets manage liquidity is both theoretically relevant and practically important. The study employs a quantitative approach, using panel data regression on a sample of 782 non-financial firms listed on the Indonesia Stock Exchange from 2013 to 2024. A total of 5,944 firm-year observations were analyzed. The empirical analysis applies the fixed effect model and Driscoll-Kraay standard errors to ensure robust statistical inference. The findings reveal a statistically significant and negative relationship between the WUI and corporate cash holdings. This suggests that during periods of high global uncertainty, Indonesian firms tend to reduce cash reserves, potentially to sustain operational activities or meet short-term obligations. The results challenge the traditional precautionary motive, which posits that firms increase cash in response to uncertainty. Instead, they highlight a context-specific liquidity behavior in emerging markets, where financial constraints and weak external financing channels may force firms to deplete cash during uncertain times. The study provides practical insights for financial managers in designing adaptive liquidity strategies, and it highlights the need for policymakers to support corporate resilience in volatile global conditions.